The Effect Of Investment Opportunity Set, Firm Age, Liquidity, And Financial Leverage On Profit Quality In LQ45 Companies In 2018 – 2022 - Prilla Mutia Indriyati; Usep Syaipudin (International Journal of Economics and Management Sciences, 2024)
This study aims to determine the impact of the IOS on the quality of profits of companies involved in LQ45 for the 2018/2022. The population of this study is comprised of LQ45 companies that are listed on the Indonesia stock exchange in 2018/2022. The sample employs a purposive sampling method in the selection of samples, this method causes the observed samples to be 41 companies that have been in existence for a period of five years. This results in a data set of 205. This research employs secondary data derived from the company's website. The hypothesis testing employed is a simple technique for regression analysis. The research results indicate that the Investment Opportunity Set and the financial leverage have a significant positive effect on the quality of earnings, the age of the company has no significant effect on the quality of earnings, and liquidity has a significant negative effect on the quality of earnings. Future researchers should consider adding variables that may influence the quality of earnings. Future additions should include other proxies for cash, such as holding cash.